Cold plasma-induced quality changes in foods and beverages and plasma’s potential use in space exploration - Warne, George (2024)
The long duration and extreme environment of space missions have led to significant challenges (weight loss and food aversion) in providing sustenance for astronauts. Traditional treatments that extend the shelf-life of food are often synonymous with reduced sensorial quality. Furthermore, future missions, such as to Mars (in the late 2030s), will increase the need for food with prolonged long shelf-life, of diverse sensory appeal. Cold plasma (non-thermally ionised gas) can reduce the negative impacts of thermal processing methods (e.g., nutritional loss, colour leaching and texture degradation), whilst also reducing microbial growth and increasing shelf-life. Cold plasma consists of free electrons, ions, reactive atomic and molecular species, and ultraviolet radiation that can generate various chemical reactions which can be controlled through various input parameters. However, there has been little research into the sensory impacts of cold plasma treatments, especially the effects on flavour, which this PhD thesis therefore sought to address.